A delayed blood transfusion reaction in a border collie. Issue 11 (2nd November 2017) - Jonas, Angela
Abstract: Blood transfusions are undertaken in most first-opinion practices and RVNs are often required to support patients both during and after a transfusion. Knowledge of the mechanisms behind transfusion reactions and the ability to recognise them are useful to any RVN supporting such patients. Development of laboratory skills and confidence to provide patient side information to the attending VS improves clinical care and is a great asset within any Practice team.